A better way to communicate: Identifying and tackling communication challenges within management teams. Issue 3 (14th March 2016) - Unknown
Abstract : Purpose: – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach: – This briefing is prepared by an independent writer who adds their own impartial comments and places the articles in context. Findings: – Heightened consideration for informal communication is needed to aid the development of trust between management team (MT) members. Informal communication should be used in out-of-work settings to allow for a more honest level of communication about MT-related issues. Practical implications: – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value: – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.